Impact of Devaluation on Balance of Trade: A Case Study of Pakistan Economy - Khan, Zeeshan; Ali, Asghar; Ali, Shahid (Asian Journal of Economic Modelling, 2016)
This study investigates the impact of devaluation on balance of trade and on the External Debt, in case of Pakistan, over the period of 1980 to 2014. The key focus of this study is to check the long run relationship among devaluation of domestic currency on Pakistan Balance of Trade and External Debt, over the period of 1980 to 2014. Further, this study also examines the short run relationship between these two variables. Moreover, this study tests the validity of J-curve in case of Pakistan. In order to examine the long run relationship between devaluation of domestic currency and balance of trade in the presence of control variables, this study uses ARDL (Autoregressive distributed lag model) econometric technique. For short run relationship between devaluation of domestic currency and balance of trade, this study uses ECM (Error Correction Mechanism). This study will recommend improved policy recommendations that whether devaluation should be carried out or not. Thus, this paper will certainly benefit the policy makers in Pakistan to deal with Exchange rates in the context of international trade and also to deal with external debt in this regards.